Movement-Related Cortical Potentials in Embodied Virtual Mirror Visual Feedback - Garipelli, Gangadhar; Rossy, Tamara; Perez-Marcos, Daniel; Jöhr, Jane; Diserens, Karin (Frontiers in Neurology, 2021)
Background: Mirror therapy is thought to drive inter-hemispheric communication, resulting in a balanced activation. We hypothesized that Embodied Virtual Mirror Visual Feedback (VR-MVF) presented on a computer screen may produce a similar activation. In this proof-of-concept study, we investigated differences in Movement-Related Cortical Potentials (MRCPs) in the Electroencephalogram (EEG) from different visual feedback of user movements in 1 stroke patient and 13 age-matched adults. Methods: A 60-year-old right-handed (Edinburgh score> 95) male ischemic stroke (left paramedian pontine, NIHSS=6) patient and 13 age-matched right-handed (Edinburgh score> 80) healthy adults (58±9 years; 6 females) participated in the study. We recorded 16-electrode EEG while participants performed planar center-out movements in two embodied visual feedback conditions: (i) Direct (movements translated to the avatar’s ipsilateral side) and (ii) Mirror (movements translated to the avatar’s contralateral side) with left (Direct Left /Mirror Left) or right (Direct Right /Mirror Right) arms. Results: As hypothesized, we observed more balanced MRCP hemispheric negativity in the Mirror Right compared to the Direct Right condition (statistically significant at the FC4 electrode; 99.9% CI: [0.81, 13]). MRCPs in the stroke participant showed reduced lateralized negativity in the Direct Left (non-paretic) situation compared to healthy participants. Interestingly, the potentials were stronger in the Mirror Left (non-paretic) compared to Direct Left case, with significantly more bilateral negativity at FC3 (95% CI: [0.758 13.2]) and C2 (95% CI: [0.04 9.52]). Conclusions: Embodied mirror visual feedback is likely to influence bilateral sensorimotor cortical sub-threshold activity during movement preparation and execution observed in MRCPs in both healthy participants and a stroke patient.